Exploring the simultaneous r-hole/p-hole bonding characteristics of a Brp interaction in an ebselen derivative via experimental and theoretical electron-density analysis. (2018) - Shukla, Rahul; Claiser, Nicolas; Souhassou, Mohamed; Lecomte, Claude; Balkrishna, Shah Jaimin; Kumar, Sangit
No abstract available